KARAKTERISTIK SOSIS TEMPE MENGGUNAKAN BERBAGAI JENIS TEPUNG - Suparma Jeki; Asnurita; Dian Pramana Putra; Wellyalina (Fakultas Pertanian, Universitas Ekasakti, 2021)
The aim of research was to determine the quality and storey of favorit consumer to tempeh sausage with using various types of flour. The method used was an exploratory method with 5 levels of treatment and 3 replications. This study uses several types of flour in making tempeh sausages that is; tapioca flour, corn flour, brown rice flour, purple sweet potato flour and sago flour. The results showed that the use of various types of flour in making tempeh sausage was favored by con summers, up to standard and also quality of sausage specified by SNI. The results of chemical analysis of the best and most preferred tempeh sausage by consumers are found in making tempeh sausage using purple weet potato flour with a water content of 55,98%, ash 1,35%, fat 21,60%, protein 13,34% and carbohydrates 6,25%.